2019
DOI: 10.1080/19475705.2019.1595178
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the possible lower ionospheric anomalies in very low frequency (VLF) signal during Honshu, 2011 and Nepal, 2015 earthquakes

Abstract: We present perturbations in very low frequency (VLF) signals received at Ionospheric & Earthquake Research Centre (IERC) (Lat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Many other statistical studies have also reported correlations between EQs and TT anomalies, with maximal shifts occurring 0-4 days prior to the main EQ event [47,[51][52][53][54][55][56][57][58]. Furthermore, some studies based on numerical simulation of the diurnal variation of the amplitude of the VLF signal, taking into consideration the characteristics of the VLF propagation path, the transmitter, and the receiver, are applied for the determination of TTs [50,59].…”
Section: Terminator Time Methods (Ttm)mentioning
confidence: 99%
“…Many other statistical studies have also reported correlations between EQs and TT anomalies, with maximal shifts occurring 0-4 days prior to the main EQ event [47,[51][52][53][54][55][56][57][58]. Furthermore, some studies based on numerical simulation of the diurnal variation of the amplitude of the VLF signal, taking into consideration the characteristics of the VLF propagation path, the transmitter, and the receiver, are applied for the determination of TTs [50,59].…”
Section: Terminator Time Methods (Ttm)mentioning
confidence: 99%
“…Later the correlation between "VLF Day Length" and seismic activity was established by [26] by using the VTX-Kolkata propagation path. The anomalies in "D layer preparation time (DLPT)" and "D layer disappearance time (DLDT)" before 1 -2 day prior to the earthquake were observed by [27] [28] [29] [30] who have presented a simultaneous and comparative study of seismogenic VLF perturbation for multiple paths and earthquakes and performed a numerical modeling. The nighttime signal fluctuations have been also investigated by [31] [32].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there have been numerous reports accumulated on the VLF/LF propagation anomalies before major EQs (see a review paper [ 19 ] and references therein, also refer to recent papers [ 20 , 21 , 22 ]) which support the AGW hypothesis of the LAIC process, and we consider that the precursory AGW acts as a responsible agent in the LAIC process.…”
Section: Introductionmentioning
confidence: 81%